2014
DOI: 10.1371/journal.pone.0103457
|View full text |Cite
|
Sign up to set email alerts
|

Multigene Molecular Phylogeny and Biogeographic Diversification of the Earth Tongue Fungi in the Genera Cudonia and Spathularia (Rhytismatales, Ascomycota)

Abstract: The family Cudoniaceae (Rhytismatales, Ascomycota) was erected to accommodate the “earth tongue fungi” in the genera Cudonia and Spathularia. There have been no recent taxonomic studies of these genera, and the evolutionary relationships within and among these fungi are largely unknown. Here we explore the molecular phylogenetic relationships within Cudonia and Spathularia using maximum likelihood and Bayesian inference analyses based on 111 collections from across the Northern Hemisphere. Phylogenies based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 88 publications
2
11
0
Order By: Relevance
“…PCR amplification was performed following Ge et al (2014) on an ABI 2720 Thermal Cycler (Applied Biosystems, Foster City, CA, USA). Primers used to amplify the internal transcribed spacer (ITS) region and the large subunit (LSU) of the ribosomal DNA and translation elongation factor 1-α (TEF1) were ITS1F/ITS4, LR0R/LR5 and 983F/1567R, respectively (Gardes and Bruns 1993;Matheny 2005;Rehner and Buckley 2005).…”
Section: Dna Extraction Pcr and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR amplification was performed following Ge et al (2014) on an ABI 2720 Thermal Cycler (Applied Biosystems, Foster City, CA, USA). Primers used to amplify the internal transcribed spacer (ITS) region and the large subunit (LSU) of the ribosomal DNA and translation elongation factor 1-α (TEF1) were ITS1F/ITS4, LR0R/LR5 and 983F/1567R, respectively (Gardes and Bruns 1993;Matheny 2005;Rehner and Buckley 2005).…”
Section: Dna Extraction Pcr and Sequencingmentioning
confidence: 99%
“…Primers used to amplify the internal transcribed spacer (ITS) region and the large subunit (LSU) of the ribosomal DNA and translation elongation factor 1-α (TEF1) were ITS1F/ITS4, LR0R/LR5 and 983F/1567R, respectively (Gardes and Bruns 1993;Matheny 2005;Rehner and Buckley 2005). Polymerase chain reaction (PCR) parameters follow those of Ge et al (2014). PCR products were purified using a QIAquick PCR purification kit (Qiagen Science, USA) and sent to Kunming Shuoqing Biotech Ltd. (Kunming, China) for sequencing.…”
Section: Dna Extraction Pcr and Sequencingmentioning
confidence: 99%
“…PCR reactions were performed on an ABI 2720 Thermal Cycler (Applied Biosystems, Foster City, CA, USA) using the published primer sets: ITS1F / ITS4 for the ITS region (Gardes & Bruns 1993), and LR0R / LR5 for the nucLSU region (Vilgalys & Hester 1990). PCR reaction parameters, sequencing reactions, and methods for editing the obtained sequences are the same as described in Ge et al (2014). The sequences produced in this study were deposited in GenBank and their accession numbers are indicated in Table 1.…”
Section: Dna Extraction Pcr Amplification and Sequencingmentioning
confidence: 99%
“…Cudonia and Spathularia (Cudoniaceae, Rhytismatales) form a morphologically and ecologically divergent clade, producing relatively large (up to 10 cm tall) clavate to fan-shaped, capitate ascomata with sterile stipes and fertile apical regions. Despite these gross morphological differences, paraphyses, asci, and ascospores of Cudonia and Spathularia are typical of Rhytismataceae and the veil that covers the developing hymenium may be homologous to the covering layer of some Rhytismataceae species(Ge et al 2014). Molecular phylogenetic work shows Cudoniaceae is nested within, and therefore synonymous with, Rhytismataceae(Lantz et al 2011, Ge et al 2014).…”
mentioning
confidence: 99%
“…Despite these gross morphological differences, paraphyses, asci, and ascospores of Cudonia and Spathularia are typical of Rhytismataceae and the veil that covers the developing hymenium may be homologous to the covering layer of some Rhytismataceae species(Ge et al 2014). Molecular phylogenetic work shows Cudoniaceae is nested within, and therefore synonymous with, Rhytismataceae(Lantz et al 2011, Ge et al 2014). This clade probably represents the transition from an endophytic or pathogenic life strategy to that of a saprotroph within Rhytismataceae.The genus Lophodermium (Rhytismataceae) comprises over 100 species predominately described from conifers(Kirk et al 2008) Larkin et al (2012).…”
mentioning
confidence: 99%